Insights into the stress corrosion cracking of solution annealed alloy 690 in simulated pressurized water reactor primary water under dynamic straining. (1st June 2018) - Kuang, Wenjun; Song, Miao; Was, Gary S.
Abstract: The intergranular attack near both stagnant and active stress corrosion crack (SCC) tips of solution annealed alloy 690 were characterized after constant extension rate tensile tests in simulated pressurized water reactor (PWR) primary water containing 18 cc H2 /kg H2 O. In both cracks, an intergranular oxide, composed of NiO and Cr2 O3, was observed beyond the crack tip with an adjacent Cr depleted grain boundary migration zone. The stagnant crack has a compact Cr2 O3 covering the crack tip and the adjacent grain boundary migration zone is deep and free of oxidation, while the active crack has porous penetrative oxide extending into the migration zone. The ability to form a compact Cr2 O3 film at the crack tip is important to the IGSCC resistance and may be dictated by the efficiency of Cr diffusion up the migrated grain boundary. When a compact Cr2 O3 film does not form at the crack tip, the Cr depleted grain boundary migration zone is subject to penetrative oxidation via the inward diffusion of oxygen, making the zone susceptible to crack propagation. Thus, even a high Cr content cannot guarantee the immunity of a Ni base alloy to SCC during dynamic straining. Graphical abstract: Image 1